2019
DOI: 10.1002/jcph.1444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ketoconazole, a CYP4F2 Inhibitor, and CYP4F2*3 Genetic Polymorphism on Pharmacokinetics of Vitamin K1

Abstract: The objective of this study was to evaluate whether cytochrome P450 (CYP)4F2 is involved in the exposure of vitamin K1 through a drug interaction study with ketoconazole, a CYP4F2 inhibitor, and a pharmacogenetic study with CYP4F2*3. Twenty‐one participants with different CYP4F2*3 polymorphisms were enrolled (8 for *1/*1, 7 for *1/*3, and 6 for *3/*3). All participants were treated twice daily for 5 days with 200 mg of ketoconazole or placebo. Finally, a single dose of 10 mg vitamin K1 was administered, plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…The rs2108622 SNP of CYP4F2 evaluated in the current study has been shown to have 50%‐75% lower in vitro activity to metabolize vitamin K 13 . The clinical effect of this CYP4F2 SNP variant has recently been confirmed, with C/T and T/T individuals exhibiting increased circulating concentrations of vitamin K of 33% and 170%, respectively, following exogenous administration of vitamin K 14 . The reduced metabolism of vitamin K (a warfarin antagonist) in individuals with these SNPs is one of several factors leading to a higher dose requirement for warfarin 15 …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The rs2108622 SNP of CYP4F2 evaluated in the current study has been shown to have 50%‐75% lower in vitro activity to metabolize vitamin K 13 . The clinical effect of this CYP4F2 SNP variant has recently been confirmed, with C/T and T/T individuals exhibiting increased circulating concentrations of vitamin K of 33% and 170%, respectively, following exogenous administration of vitamin K 14 . The reduced metabolism of vitamin K (a warfarin antagonist) in individuals with these SNPs is one of several factors leading to a higher dose requirement for warfarin 15 …”
Section: Discussionmentioning
confidence: 52%
“…The rs2108622 SNP of CYP4F2 evaluated in the current study has been shown to have 50%-75% lower in vitro activity to metabolize vitamin K. 13 The clinical effect of this CYP4F2 SNP variant has recently been confirmed, with C/T and T/T individuals exhibiting increased circulating concentrations of vitamin K of 33% and 170%, respectively, following exogenous administration of vitamin K. 14 The reduced metabolism of vitamin K (a warfarin antagonist) in individuals with these SNPs is one of several factors leading to a higher dose requirement for warfarin. 15 In contrast to the 170% increase in vitamin K concentrations, 14 subjects with the T/T genotype (lowest activity) in this meta-analysis of genotyping data from subjects administered brincidofovir across 6 phase 1 studies (Table S1) showed a relatively modest increase in brincidofovir exposure (up to 36%). The modest effect of the T genotype on brincidofovir exposure is likely due to the dual pathways for brincidofovir elimination (∼40% oxidation and ∼40% hydrolysis 20 ).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It is reported that most CYP enzymes exhibit marked genetic polymorphism, including copy number variation, missense mutation, insertion, deletion, and most of these genetic variations can affect the protein expression level or drug metabolic activity of enzyme. Clinical evidence has confirmed the apparent correlation between genetic polymorphisms of CYP and adverse drug reactions (ADRs), especially for drugs with narrow therapeutic windows (5)(6)(7).…”
Section: Introductionmentioning
confidence: 97%